Birth Tourism Is Associated with Fewer Neonatal Intensive Care Unit Admissions: A Healthy Migrant Effect? - Lim, Jina; Sun, Wang-Dar; Zhang, Lishi; Mikhael, Michel (American Journal of Perinatology, 2020)
Objective This work aimed to study perinatal, maternal, and neonatal characteristics of birth tourism (BT) mother–baby dyads and the rate of neonatal intensive care unit (NICU) admissions of BT infants.Study Design Retrospective study at a regional perinatal center comparing BT mother–baby dyads to all dyads. BT infants admitted to the NICU were compared with a randomly selected group of infants admitted to the NICU during the same time period.Results A total of 1,755 BT dyads were identified over 4 years. BT mothers were older (32 vs. 28 years, p < 0.0001), more likely to carry multiples (5.5 vs. 1.4%, p < 0.0001), deliver via cesarean section (40 vs. 34%, p < 0.0001), and require postpartum intensive care (0.6 vs. 0.1%, p < 0.0001). BT infants had significantly fewer NICU admissions 96 (5.5%) versus 3,213 (11.3%; p < 0.0001). There were no statistically significant differences in NICU course and outcome between BT and non-BT control infants.Conclusion Birth tourism is associated with unique determinants of health. In our study, there were fewer NICU admissions, potentially explained by the healthy migrant effect.Key Points
Keywords: birth tourism; healthy migrant hypothesis; neonate; neonatal intensive care unit